Peripartum cardiomyopathy: An analysis of clinical profiles and outcomes from a tertiary care centre in southern India. (December 2020) - Binu, Aditya John; Rajan, Sudha Jasmine; Rathore, Swati; Beck, Manisha; Regi, Annie; Thomson, Viji Samuel; Sathyendra, Sowmya
Peripartum cardiomyopathy is a syndrome of maternal heart failure with decreased left ventricular ejection fraction affecting maternal and fetal well-being. We analysed clinical profiles and outcomes in women with peripartum cardiomyopathy enrolled retrospectively from a tertiary care centre in southern India (1 January 2008–31 December 2014). The incidence of peripartum cardiomyopathy was one case per 1541 live births. Fifty-four women with a mean age of 25.5 years and mean gestational age of 35.4 weeks were recruited; 35 were primigravidae. Maternal and fetal deaths occurred in 9.3% and 24.1% of subjects, respectively. Mild-to-moderate maternal anaemia (80–110 g/L) was associated with fetal mortality (p = 0.02). Reduced left ventricular ejection fraction (<30%, p = 0.04) and cardiogenic shock (p = 0.01) were significantly associated with adverse maternal outcomes. Forty per cent of women were followed up after 24.2 ± 17.7 months, and in these women a significant increase in left ventricular ejection fraction was seen (mean 16.4%, p < 0.01); all were asymptomatic. Peripartum cardiomyopathy with poor left ventricular ejection fraction and shock is associated with adverse maternal outcomes, while non-severe maternal anaemia predisposes to adverse fetal outcomes. Significant left ventricular ejection fraction recovery occurred on follow-up.